Climate Village Adaptation in Sindang Jaya Village and South Manokwari Waroser - Rony Gerits; Rudi A Maturbongs; Rima Herlina Siburian (Universitas Muhammadiyah Sorong, 2021)
The purpose of writing is to compare the implementation of climate village program adaptation activities in Sindang Jaya and Waroser villages, South Manokwari Regency. This study uses a descriptive method with multiple regression analysis to determine the factors that most influence the implementation of adaptation activities in these two adjacent villages. This study indicates that in Kampung Sindang Jaya and Kampung Waroser, there are several adaptation activities, including drought, flood, and landslide control, actions to increase food security, and disease control activities. The age variable is a value that partially negatively affects climate change adaptation activities in Sindang Village. In contrast, for Waroser Village, age, education, and information media variables significantly affect people's attitudes towards climate change adaptation activities.